2002
DOI: 10.1002/1521-3838(200211)21:5<493::aid-qsar493>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prediction of Human Intestinal Absorption

Abstract: This work describes the modeling of human intestinal absorption using one-and two-descriptor nonlinear models. Molecules with known transport mechanisms other than passive transport were removed from the dataset. The human intestinal absorption data were fitted to symmetric and asymmetric sigmoidal curves and surfaces that were based on the arctangent function. The descriptors employed in the models are the sum of hydrogen bond donors and acceptors and the calculated SlogP octanol-water partition coefficient. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…According to the above analysis, we found that no rules based on molecular properties can effectively identify these unfavorably bioavailable compounds. Figure S3 in the Supporting Information shows the scatter plot of bioavailability (%F) vs intestinal absorption (%HIA) [12][13][14] for 214 compounds. The %HIA values for these 214 compounds are listed in Table S3 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…According to the above analysis, we found that no rules based on molecular properties can effectively identify these unfavorably bioavailable compounds. Figure S3 in the Supporting Information shows the scatter plot of bioavailability (%F) vs intestinal absorption (%HIA) [12][13][14] for 214 compounds. The %HIA values for these 214 compounds are listed in Table S3 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…(1) Hydrophobicity Descriptor. The experimental log D values at pH 7.4 for all compounds were obtained from the literature. , ,, It should be noted that the log D values for the same compound might exist with some differences in a different reference. For example, the log D values for atenolol from refs and are −1.29 and −2.14, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…(2296) The predictions were improved if the chemicals were classified according to similarity and the sigmoidal dependence was applied to the subsets. (2297)…”
Section: Comparison With Other Approachesmentioning
confidence: 99%